An UWB Vivaldi Antenna with the Enhanced Functionalities Through the use of DGS and Dielectric Lens - Belen, Mehmet Ali; Evranos, Ilhan Omer; Gunes, Filiz; Mahouti, Peyman (IEEE, 2017)
Nowadays UWB antennae have become popular due to the growing need for both the UWB ground and space communication. In this work, an UWB Vivaldi antenna is proposed with the enhanced functionalities through the use of DGS and dielectric lens for to be used for both ground and space communications. Performance enhancement of an UWB Vivaldi antenna is worked out on Roger 4350B substrate (epsilon(r)=3.66, ran delta=1.58mm) within the bandwidth of 1-14 GHz using the CST Microwave Studio environment. For the purpose, Defected Ground Structure (DGS) and dielectric lens are used in the low and high frequency regions, respectively. In this work, Vivaldi antenna structure is particularly preferred due to its cost-effective and simple manufacturing over 1 GHz. Furthermore, performance enhancement of the antenna also verified experimentally as compared with the simulated return loss and radiation gain characteristics within the 1-14 GHz bandwidth.
Keywords: DGS; Vivaldi Antenna; Dielectric Lens; SLOT ANTENNA; Engineering; Remote Sensing